Sonazoid-enhanced ultrasonography: comparison with CT/MRI Liver Imaging Reporting and Data System in patients with suspected hepatocellular carcinoma - Hwang, Jeong Ah; Jeong, Woo Kyoung; Min, Ji Hye; Kim, Yeun-Yoon; Heo, Nam Hun; Lim, Hyo Keun (Ultrasonography (Seoul, Korea), 2021)
Purpose: The aim of this study was to evaluate the association of contrast-enhanced ultrasound (CEUS) features using Sonazoid for liver nodules with Liver Imaging Reporting and Data System (LI-RADS) categories and to identify the usefulness of Kupffer-phase images.Methods: This retrospective study was conducted in 203 patients at high risk of hepatocellular carcinoma (HCC) who underwent CEUS with Sonazoid from 2013 to 2016. Nodule enhancement in the arterial, portal venous, late, and Kupffer phases; CEUS LI-RADS major features; and Kupffer-phase defects were evaluated. According to the computed tomography/magnetic resonance imaging (CT/MRI) LI-RADS v2018, all nodules were assigned an LR category (n=4/33/99/67 for LR-M/3/4/5) and comparisons across LR categories were made. We defined modified CEUS LI-RADS as using Kupffer-phase defects as an alternative to late and mild washout in CEUS LI-RADS and compared the diagnostic performance for HCC.Results: On CEUS of 203 nodules, 89.6% of CT/MRI LR-5 and 85.9% of LR-4 nodules showed hyperenhancement in the arterial phase, while 57.6% of LR-3 nodules showed hyperenhancement. Among the CT/MRI LR-5 nodules that showed arterial phase hyperenhancement or isoenhancement, 59.7% showed hypoenhancing changes from the portal venous phase, 23.9% from the late phase, and 13.4% additionally in the Kupffer phase. The modified CEUS LI-RADS showed higher sensitivity than CEUS LI-RADS (83.2% vs. 74.2%, P=0.008) without compromising specificity (63.6% vs. 69.7%, P=0.500).Conclusion: The Kupffer phase best shows hypoenhancing changes in LR-5 lesions and is expected to improve the sensitivity for HCC in high-risk patients.